2014
DOI: 10.1002/jpln.201200061
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation of alpine plants: Implications from leaf N : P stoichiometry and leaf δ15N

Abstract: Nitrogen (N) deposition can affect grassland ecosystems by altering biomass production, plant species composition and abundance. Therefore, a better understanding of the response of dominant plant species to N input is a prerequisite for accurate prediction of future changes and interactions within plant communities. We evaluated the response of seven dominant plant species on the Tibetan Plateau to N input at two levels: individual species and plant functional group. This was achieved by assessing leaf N : P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 34 publications
3
17
0
1
Order By: Relevance
“…These relationships suggest that leaf N and P stoichiometry, as the endogenous nutrition, has shaped the morphological performances of leaves and stem, supporting the previous report that N and P frequently limit plant growth39. However, we also found that these associations among indices showed huge differences.…”
Section: Discussionsupporting
confidence: 90%
“…These relationships suggest that leaf N and P stoichiometry, as the endogenous nutrition, has shaped the morphological performances of leaves and stem, supporting the previous report that N and P frequently limit plant growth39. However, we also found that these associations among indices showed huge differences.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that plant species differ in N acquisition strategies in alpine meadows (Xu et al, ), which suggests that N input may have the potential to affect species composition and abundance in alpine meadows (Xu et al, ). Plant species composition has altered substantially in recent decades due to the intensive degradation of alpine grasslands and differences among species in the efficiency of N uptake in N‐limited ecosystems (Schleuss et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf N and P stoichiometry have certain indicative effects on the growth rate, adaptation strategy, nutrient limitation, and community function of plants [1][2][3][4]. Leaf stoichiometry is likely affected by changes in the environment, including biotic and abiotic factors [5,6].…”
Section: Introductionmentioning
confidence: 99%